Determinan Faktor yang Berhubungan dengan Penyakit Tidak Menular pada Jemaah Haji Provinsi Aceh - Saidah Saidah; Hafnidar A.Rani; Mawardi Mawardi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Hajj is a worship that requires healthy physical and mental strength so that it can run all harmoniously in the Hajj, considering the long waiting time of the Hajj and the majority of pilgrims consisting of high-risk age groups and suffering from various diseases. This type of research is analytic using a cross sectional design. The population in this study were pilgrims who were examined health in 2018 as many as 4,651. Sample is the total of the population. Data collection is done using secondary data. Data was analyzed by statistical logistic regression test with stata. The results of the study revealed that 58.2% of respondents suffered from non-communicable diseases (NCD). Statistical test results found that factors related to NCD were age (OR = 1.6; P value = 0,0001), work (OR = 1.1; P value = 0.012), smoking (OR = 1.6; P value = 0,0001), central obesity (OR = 1.4; P value = 0,0001) and body mass index (BMI) (OR = 4.0; P value = 0,0001). The conclusion of the study is the variable BMI (obesity) is the most associated factor with the incidence of NCD in pilgrims with an OR of 2.1 times (CI; 1.96-2.39) so that the risk of suffering from NCD is 2 times more dominant compared to other variables. It is recommended to the government to be able to increase cooperation between the ministry of health and the ministry of religion to provide guidance, monitoring and evaluation of the implementation of health services for pilgrims